Trauma encefálico e torácico em cães - Rocha, Gustavo Souza (Universidade Federal do Tocantins, 2023)
The Supervised Curricular Internship, executed in the area of Medical Clinic and Small Animal Surgery Clinic, was carried out in the clinic Casa da Ração Atividades veterinárias, located in the city of Marabá in the state of Pará, in the period between August 15 and October 27, 2022. The referred internship counted 390 hours, having as supervisor and advisor M.V. Dra Erycka Carolina França and Prof. Dr. Priscilla Macedo Souza respectively. This report contains a description of the internship site, the activities developed during this period, the casuistry followed, and the procedures performed. In addition, this report contains a case report with the theme of brain and chest trauma in dogs in a three-month old pit-bull dog.